Quantitative analysis of microbiota in saliva, supragingival, and subgingival plaque of Chinese adults with chronic periodontitis - He, Jiayan; Huang, Wujing; Pan, Zhiwen; Cui, Honghua; Qi, Ganggang; Zhou, Xueping; Chen, Hui (Clinical oral investigations, 2012)
Objective The aim of this study was to determine the profiles of periodontopathogenic bacteria in a Chinese population using quantitative real-time polymerase chain reaction (qRT-PCR). Materials and methods Twenty-four periodontally healthy Chinese subjects and 60 patients with chronic periodontitis (CP) were enrolled in this cross-sectional study. qRT-PCR was used to quantify Aggregatibacter actinomycetemcomitans , Fusobacterium nucleatum , Porphyromonas gingivalis , and Prevotella intermedia as well as total bacterial counts from 252 samples collected from the saliva, supragingival plaque, and subgingival plaque of all 84 subjects. Results The detection frequency of A. actinomycetemcomitans was less than 50%. F. nucleatum was detected in all subjects and CP patients had higher bacterial loads than healthy subjects. The median proportion of F. nucleatum was significantly higher in subgingival plaque than in supragingival plaque and saliva. P. gingivalis and P. intermedia had higher detection frequencies and bacterial loads in CP patients than in healthy subjects. The median proportion of P. gingivalis was significantly different among the three intraoral locations in the CP group and its proportion in subgingival plaque was 9.01%. Moreover, strong positive Spearman’s correlations were found in A. actinomycetemcomitans , P. gingivalis , and P. intermedia counts across the three intraoral locations. Conclusion The presence and bacteria loads of these four bacteria in this Chinese population are similar to those from other populations. Clinical relevance Examination of bacterial detection frequency and loads in Chinese adults may assist microbial studies of periodontal disease and will shed light on periodontal disease diagnosis and treatment using antibiotics in the Chinese population.